CG Collaborative Teaching (CGCT) for ELC231 (20224 semester) - Lau, Kimberley Yih Long; Runggol, Christine Jacqueline (UiTM Sarawak, 2024)
Collaborative Teaching, also known as cooperative teaching or team teaching, refers to teaching approaches which usually involve local or (and) international academicians, experts or industrial practitioners. This approach goes in tandem with with the Malaysia Higher Education Blueprint (2015-2025) which aims to ‘reduce the silo approach in operations involving all departments, as well as strengthening the relationship between IPT, industry and the community’.